Dynamics of Immigrant Entrepreneurship in Romania - Grosu, Raluka (Economy of Regions, 2015)
Immigrant entrepreneurship may represent a means for diminishing the negative effects specific to the migration phenomenon and for emphasising the positive ones, contributing to the development of strong regions. The present paper outlines a series of information gathered through an ongoing complex and comprehensive research on immigrant entrepreneurship in Romania, approached from economic, social, institutional, and cultural perspectives. The major aim of the research is to provide a wide image on the investigated phenomenon in order to raise awareness among policymakers of its importance and complexity. The paper puts forward a series of empirical results obtained through the development of an econometrical analysis of statistical data and interview-based research. Results highlight a strong positive correlation between the number of enterprises (total and newly registered) and the number of immigrants in Romania. In this context, the hypothesis of the existence of another variable - especially related to the socio-economic and legislative environments - with an impact on both the number of enterprises and the one of immigrants may arise. Furthermore, in-depth explanations are provided by the carried out interviews. Debated issues refer to motivations, incentives, and obstacles in business development, cultural and social norms, commercial infrastructure, regulatory aspects, etc.